Elevated Snail Expression Mediates Tumor Progression in Areca Quid Chewing-Associated Oral Squamous Cell Carcinoma via Reactive Oxygen Species - Lee, Shiuan-Shinn (Public Library of Science, 2013)
BACKGROUND: Snail is an important transcription factor implicated in several tumor progression and can be induced by reactive oxygen species (ROS). Areca quid chewing is a major risk factor of oral squamous cell carcinoma (OSCC). Therefore, we hypothesize that the major areca nut alkaloid arecoline may induce Snail via ROS and involve in the pathogenesis of areca quid chewing-associated OSCC. METHODOLOGY/PRINCIPAL FINDING: Thirty-six OSCC and ten normal oral epithelium specimens were examined by immunohistochemistry and analyzed by the clinico-pathological profiles. Cytotoxicity, 2′, 7′-dichlorofluorescein diacetate assay, and western blot were used to investigate the effects of arecoline in human oral keratinocytes (HOKs) and oral epithelial cell line OECM-1 cells. In addition, antioxidants N-acetyl-L-cysteine (NAC), curcumin, and epigallocatechin-3 gallate (EGCG) were added to find the possible regulatory mechanisms. Initially, Snail expression was significantly higher in OSCC specimens (p<0.05). Elevated Snail expression was associated with lymph node metastasis (p = 0.031) and poor differentiation (p = 0.017). Arecoline enhanced the generation of intracellular ROS at the concentration higher than 40 µg/ml (p<0.05). Arecoline was also found to induced Snail expression in a dose- and time-dependent manner (p<0.05). Treatment with NAC, curcumin, and EGCG markedly inhibited arecoline induced Snail expression (p<0.05). CONCLUSION/SIGNIFICANCE: Our results suggest that Snail overexpression in areca quid chewing-associated OSCC is associated with tumors differentiation and lymph node metastasis. Arecoline-upregulated Snail expression may be mediated by ROS generation. In addition, arecoline induced Snail expression was downregulated by NAC, curcumin, and EGCG.